Решение пространственной контактной задачи термоупругости применительно к зубчатой передаче с точечным контактом - Тариков, Г. П.; Пархоменко, В. Н.; Комраков, В. В. (НТУ "ХПИ", 2014)
В работе рассмотрено решение пространственной контактной задачи с учетом температуры применительно к зубчатому зацеплению. Выведены формулы для определения контактных напряжений возникающих на площадке контакта. Приведен числовой пример решения задачи.

In this paper we consider the solution of three-dimensional contact problem with influence of temperature applied to the gear. The formulas were found determine the contact stresses appeared on the contact area. Numerical example of solving the problem was given.
Solution of three-dimensional thermoelasticity contact problem applied to the point contact gear
Keywords: площадка контакта; шестерня; колесо; контактное напряжение; contact problem; contact area; gear; wheel; thermoelasticity; point contact; contact stress